Estimativa do ponto de saturação de nitrogênio e fósforo para Eichhornia crassipes (Mart.) Solms e Salvinia molesta Mitchell em mesocosmos utilizados para o tratamento de efluente de aquicultura - Peixoto Henares, Matheus Nicolino [UNESP]; Monteiro Camargo, Antonio Fernando [UNESP] (FapUNIFESP (SciELO), 2014)
Aim: To evaluate the growth of Eichhornia crassipes (Mart.) Solms and Salvinia molesta Mitchell in tanks used for treating aquaculture effluent and compare the results with literature data in order to estimate the nutrients saturation point. Methods: An experiment with six rectangular fiberglass tanks were separated in two treatments, inflow and outflow (higher and lower nutrient concentration), and the two macrophytes above cited was carried out during 50 days. A floating quadrat with 0.25 m2 of E. crassipes and S. molesta at inflow and outflow of the tanks was collected weekly for fresh mass measurement. At the beginning and end of the experiment samples of macrophytes were oven-dried at 60 °C until constant weight to determine the dry mass. Dry mass of plants was estimated by a simple linear regression analysis between fresh mass and dry mass (DM). Results: The N and P concentrations were significantly higher (P<0.05) in the inflow (mean of 0.66 mg L–1 and 233.6 mg L–1, respectively) than in the outflow of the tanks (mean of 0.38 mg L–1 and 174.7 mg L–1, respectively). However, no significantly different plant growth was observed for either higher or lower concentration. For both higher and lower nutrient concentrations, the biomass gain for E. crassipes was, respectively, 428.5 and 402.7 g DM.m2. For S. molesta, biomass gain was 135.2 and 143.1 g DM.m2, in the higher and lower concentrations, respectively. Others studies reported high growth of E. crassipes and S. molesta in concentrations of nitrogen (0.14 – 0.18 mg L–1) and phosphorus (14.2 – 77.0 mg L–1) lower than this study. Conclusion: The comparison of E. crassipes and S. molesta growth in this study with others allow us to assume that the saturation point of E. crassipes should be 0.26 mg L–1 of nitrogen and 77 mg L–1 of phosphorus and for S. molesta below 0.19 mg L–1 of nitrogen and 15.1 mg L–1 of phosphorus.
Estimating nitrogen and phosphorus saturation point for Eichhornia crassipes (Mart.) Solms and Salvinia molesta Mitchell in mesocosms used to treating aquaculture effluent
Keywords: Aquatic macrophytes; Effluents; Freshwater prawn; Growth; Nutrients